Βιβλιοκρισία: Knighthoods of Christ: Essays on the History of the Crusades and the Knights Templar, Presented to Malcolm Barber, επιμ. NORMAN HOUSLEY, Aldershot: Ashgate / Abingdon & New York: Routledge, 2007 (αρχική δημοσίευση) / 2017 (ηλεκτρονική έκδοση) - ΧΡΥΣΗΣ Νικόλαος (Byzantina Symmeikta, 2020)
Βιβλιοκρισία: Knighthoods of Christ: Essays on the History of the Crusades and the Knights Templar, Presented to Malcolm Barber, επιμ. Norman Housley, Aldershot: Ashgate / Abingdon & New York: Routledge, 2007 (αρχική δημοσίευση) / 2017 (ηλεκτρονική έκδοση)